Analytical model for the estimation of the hygrothermal residual stresses in generally layered laminates. (15th April 2021) - Polyzos, E.; Van Hemelrijck, D.; Pyl, L.
Abstract: Delamination tests are commonly used for the evaluation of the fracture toughness. The analytical formulation used for the tests is derived for homogeneous symmetric laminates with a crack propagating in the middle plane. The difference between manufacturing and operating temperature and moisture conditions is neglected. The present paper considers geometries with asymmetric generic stacking (asymmetric and unbalanced) that are under the influence of hygrothermal effects. Explicit formulas are derived for the parameters associated with delamination tests that are of practical interest for in-situ monitoring. The results depict a good agreement with Finite Element analyses. Highlights: Explicit formulas for generally layered laminates with residual thermal stresses. Comparison of Finite Element models and analytical models. Effect of residual thermal stresses on the compliance of delamination tests.